(untitled) (Docentes 2.0 Journal, 2023)
Implementing a Quality Assurance System increases the growing competitiveness among the Civil Aeronautics Instruction Centers, seeking to improve the effectiveness of aeronautical professionals in the competitive and reduced environment we have in our country today. The essay’s objective proposes a structure for continuous improvement in the training of professionals in the aeronautical field, which meets the basic requirements of ISO9001:2015, as well as the regulations used in civil aeronautics. The analytical-deductive method was applied, humanist paradigm, qualitative approach, interpretive type, and topic narrative design, examining primary and secondary sources of information, obtaining a proposal for a basic structure of control and process improvement, applied in aeronautical instruction centers that allow raising awareness of the commitment to improve educational policies and processes, with comprehensive training for the development and improvement of education in civil aviation.